Sucrose and Glycerol Additives: A Way to Tune the Biological and Physicochemical Properties of Agarose Hydrogels? - Victor C. Igbokwe; Vincent Ball; Nour‐Ouda Benzaamia; Simon Gree; Sophie Hellé; Juliette Soubirou‐Blot; Corinne Nardin; Lydie Ploux (Macromolecular Materials and Engineering)
Abstract Sucrose and glycerol have gained attention as additives for hydrogels, owing to their capacity to exert considerable influence over the physicochemical, mechanical, and biological characteristics of these materials. Herein, these effects on agarose hydrogels (AHs) are explored. A series of AHs are synthesized using sucrose (30% and 300% w/v) and glycerol as additives. The storage modulus (10.0–13.7 kPa) and hydrophilicity of the hydrogels (contact angle < 50°) do not vary significantly with sucrose or glycerol addition. However, sucrose enhances the hydration capacity of the hydrogels by up to 170%, whereas glycerol reduces it. Interestingly, sucrose and glycerol individually do not have bacteriostatic effects against Staphylococcus epidermidis, but their combination significantly (p ≤ 0.001) inhibits the growth of both S. epidermidis and Pseudomonas aeruginosa by 63% and 29%, respectively, in comparison to native agarose. Cytotoxicity testing on NIH/3T3 murine fibroblasts reveals that sucrose increases cell viability up to 98%, while glycerol reduces it below 60%. Overall, these hydrogels hold promise for antibacterial biomedical applications as wound dressing materials and surface coatings for medical devices and can also be used to formulate bioinks for 3D bioprinting.